LEGAL PROTECTION OF BUYERS THAT IS GOOD TO GO TO THE LAND BECAUSE BLOCKING BY ANOTHER PART (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
From the research results Legal protection against buyers with good intentions due to blocking by other parties, namely buyers with good intentions must be protected because legal protection to buyers with good intentions has been regulated in MA Jurisprudence dated March 29, 1982 Number 1230 K / Sip / 1980, confirming that buyers those with good intentions must get legal protection. A good intention buyer is if he has fulfilled the material requirements and formal conditions at the time of making a sale and purchase of land, then the legal act of buying and selling gets legal protection because it is considered to have fulfilled the legal requirements. The right of buyers with good intentions must be fulfilled, so that the process of returning names must be processed by the parties concerned. Legal certainty for buyers with good intentions with the blocking of buying and selling objects by other parties, namely buyers with good intentions must obtain legal certainty in which the element of good faith is honesty, obligations have been fulfilled and have no immoral purpose. Blocking is limited to providing legal certainty regarding holders of land rights and is based on ATR Minister Regulation / Head of BPN No. 13 of 2017 Regarding the Procedures for Blocking and Sita, especially in Article 13, explains in full to provide legal certainty to the public, especially buyers who have good intentions in the process of transferring land rights.